(NmATEMATI^ESKAQ TEORIQ OPTIMALXNOGO \KSPERIMENTA (B:s (Nu^EBNOE POSOBIE (B/s - (NeRMAKOW(B, (NsERGEJ mIHAJLOWI^s; (NvIGLQWSKIJ(B, (NaNATOLIJ aLEKSANDROWI^s; (NmAR^UK(B, (Ng(B.(Ni(B.s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1987)
(NbIBLIOGR(B.: (NS(B. 315-316 (52 (NNAZW(B.)s
(NpREDM(B. (NUKAZ(B.: (NS(B. 317-318s
Keywords: (NmATEMATI^ESKIE METODYs; (NpLANIROWANIEs; (N|KSPERIMENTs